2010
DOI: 10.1016/j.crci.2010.03.034
|View full text |Cite
|
Sign up to set email alerts
|

Curvature of the lanthanide contraction: An explanation

Abstract: This is an electronic version of an article published in Comptes Rendus Chimie. 2010, 13, 849-852 This is an electronic version of an article published in Comptes Rendus Chimie. 2010, 13, 849-852. Comptes Rendus Chime is available online at: http://dx.doi.org

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 20 publications
2
29
0
Order By: Relevance
“…The contraction along the lanthanide series has been reported as quadratic by Quadrelli (2002); this was confirmed by Seitz et al (2007) for an isostructural series of trivalent La-Lu complexes (R 2 > 0.99); they also showed that the relation may be derived theoretically from Slater's model of atomic shielding constants (Slater, 1930). This was expanded by Raymond et al (2010) using hydrogen-type wavefunctions. We verify these results below.…”
Section: Research Papersmentioning
confidence: 66%
See 2 more Smart Citations
“…The contraction along the lanthanide series has been reported as quadratic by Quadrelli (2002); this was confirmed by Seitz et al (2007) for an isostructural series of trivalent La-Lu complexes (R 2 > 0.99); they also showed that the relation may be derived theoretically from Slater's model of atomic shielding constants (Slater, 1930). This was expanded by Raymond et al (2010) using hydrogen-type wavefunctions. We verify these results below.…”
Section: Research Papersmentioning
confidence: 66%
“…The curvature of the lanthanide contraction for trivalent ions has been investigated by Quadrelli (2002), Seitz et al (2007) and Raymond et al (2010). Quadrelli (2002) gave the mean bond length of the three equatorial bonds and that of the six other bonds as a function of the number of electrons in the f shell for a series of isotypical compounds in which the lanthanide ions are [9]-coordinated.…”
Section: Observed F-block Contraction For Cations Bonded To O 2àmentioning
confidence: 99%
See 1 more Smart Citation
“…Raymond et al 2010). This results in a systematic variation of speciation in seawater dominated by complexes with carbonate ions (Chantrell and Byre, 1987).…”
Section: Introductionmentioning
confidence: 99%
“…Under typical geological conditions they occur as trivalent cations with the exception of Ce (also often tetravalent) and Eu (often also divalent). Their valence electron structures are similar, and cationic radii vary quadratically from the large La 3+ to the small Lu 3+ due to the lanthanide contraction (Raymond et al , 2010; Seitz et al , 2007). This contraction, together with its effect on mesoscale molecular interactions (Ferru et al , 2016) leads to small yet gradual and predictable changes in their chemical behaviour.…”
Section: Introductionmentioning
confidence: 99%